THE ROLE OF MOTIVATION IN MEDIATING THE EFFECT OF PLACEMENT AND DISCIPLINE ON EMPLOYEE PERFORMANCE AT UPTD PPRD BALI PROVINCE IN GIANYAR DISTRICT - Desak Putu Ayu Melbi Suari; Ida Bagus Udayana Putra; I Made Suniastha Amerta (Universitas 17 Agustus 1945 Surabaya, 2022)
Human Resources has become an important global issue and affects the government system in Indonesia. This condition is because human resources act as implementers of various activities carried out by the organization. Performance is the result of work in quality and quantity achieved by an employee in carrying out his duties. Good employee performance will affect organizational performance. Factors that affect performance include compensation, employee placement, work environment, work motivation, organizational culture, leadership, work discipline, job satisfaction. This study is devoted to assessing the effect of placement, discipline and motivation on the performance of civil servants at the UPTD PPRD Bali Province in Gianyar Regency. Through research with a sample of 35 civil servants with survey methods and data collection instruments in the form of a 5 (five) Likert questionnaire containing questions about indicators that affect performance including placement, discipline and motivation. The data used are primary and secondary data, both quantitative and qualitative data. The data analysis method used descriptive analysis and inferential analysis using the Partial Least Square (PLS) approach. The results showed that the placement had a positive and significant effect on performance. Placement has a positive and significant effect on motivation. Discipline has a positive but not significant effect on motivation. Discipline has a negative and insignificant effect on performance. Motivation has a positive and significant effect on employee performance. Motivation partially mediates the effect of placement on employee performance. Motivation cannot mediate the effect of discipline on employee performance. Keywords: Placement, Discipline, Motivation, Performance